An introduction to penology : punishment, prisons and probation - Burke, Lawrence; Gosling, Helena (Thousand Oaks : SAGE Publications Ltd, 2022)
"This book is designed to provide a concise, informative, scholarly text that will speak to a variety of audiences interested in how the notion of punishment, plays out in community and custodial settings with people who have broken the law. With a particular focus on prisons and probation, the book provides an opportunity for readers to critically engage with the concept of punishment (in theory and practice) and consider different ways in which we, as a society, can respond to lawbreaking"--
Includes bibliographical references and index.
Keywords: penology